Detection of antibiotic-resistant canine origin Escherichia coli and the synergistic effect of magnolol in reducing the resistance of multidrug-resistant Escherichia coli - Tong, Yin-Chao; Zhang, Yi-Ning; Li, Peng-Cheng; Cao, Ya-Li; Ding, Dong-Zhao; Yang, Yang; Lin, Qing-Yi; Gao, Yi-Nuo; Sun, Shao-Qiang; Fan, Yun-Peng; Liu, Ying-Qiu; Qing, Su-Zhu; et al. (Frontiers in Veterinary Science, 2023)
Background: The development of antimicrobial resistance in the opportunistic pathogen Escherichia coli has become a global public health concern. Due to daily contact, dogs kept as pets share the same E. coli with their owners. This study aimed to detect the prevalence of antibiotic-resistance of canine origin E. coli in Shaanxi province and explore the inhibition effect of magnolol combined with cefquinome on MDR E. coli, so as to provide evidence for use of antibiotics. Methods: Canine fecal samples were collected from animal hospitals. The E. coli isolates were separated and purified using indicator media and polymerase chain reaction (PCR). Drug-resistance genes (aacC2, ant(3’)-Ⅰ, aph(3’)-Ⅱ, aac(6’)-Ⅰb-cr, aac(3’)-Ⅱe, blaKPC, blaIMP-4, blaOXA, blaCMY, blaTEM-1, blaSHV, blaCTX-M-1, blaCTX-M-9, Qnra, Qnrb, Qnrs, TetA, TetB, TetM, Ermb) were detected by PCR. The minimum inhibitory concentration (MIC) was determined for 10 antibiotics. Synergistic activity of magnolol and cefquinome against multidrug-resistant (MDR) E. coli strains was investigated using checkerboard assays, time-kill curves, and drug-resistance curves. Results: A total of 101 E. coli strains were isolated from 158 fecal samples collected. MIC determinations showed that 75.25% (76/101) of the E. coli strains were MDR. A total of 22 drug-resistance genes were detected among the 101 strains. The blaTEM-1 gene exhibited the highest detection rate (89.77%). The TetA and Sul gene also exhibited high detection rate (66.34% and 53.47% respectively). Carbapenem-resistant E. coli strains were found in Shangluo and Yan’an. Additionally, in MDR E. coli initially resistant to cefquinome, magnolol increased the susceptibility to cefquinome, with an FICI (Fractional Inhibitory Concentration Index) between 0.125 and 0.5, indicating stable synergy. Furthermore, magnolol enhanced the killing effect of cefquinome against MDR E. coli. Resistance of MDR E. coli to cefquinome decreased markedly after treatment with magnolol for 15 generations. Conclusion: Our study indicates that antibiotic-resistance E. coli has been found in pet dogs. After treatment with magnolol, the sensitivity of MDR E. coli to cefquinome was enhanced, indicating that magnolol reverses the resistance of MDR E. coli. The results of this study provide reference for the control of E. coli resistance. Keywords: Canine, MDR E. coli, drug-resistance detection, magnolol, antibiotics adjuvant